Form Design in Web Application Using the Three-Layer Model (TLM) : A Checklist Development - Zanariah, Idrus (2005)
The objectives of end users visiting web site are generally for information retrieval whereas for web application, users have specific goals, which are to complete tasks successfully. Nevertheless, some online job applications do not meet task-based orientation design and this resulted in users’ frustration. Therefore, for the purpose of reducing the frustration and providing guidelines, a form design checklist was developed. In addition, an investigation of the current state of web form design among Malaysian developers was also conducted. A four-step methodology was followed; understand Three-Layer Model (TLM) concept, develop checklist based on guidelines, collect and identify existing Malaysian web forms, and finally, validate checklist and compare the collected web forms with the Three-Layer Model. In validating the checklist, 15 respondents performed three sets of tasks: pre-test, post-test and comparing three pre-selected online forms. Findings indicated that students designed better web forms after learning about the TLM and this suggests that the checklist provided guidance in designing better web form. Results also pointed out that the current state of web forms designed by Malaysian does not meet task-based orientation design.